2019
DOI: 10.1073/pnas.1808635115
|View full text |Cite
|
Sign up to set email alerts
|

Interaction design of community-driven environmental projects (CDEPs): A case study from the Anacostia Watershed

Abstract: Water is becoming an increasingly precious resource across the world, but citizens can help ensure good-quality water by helping to manage their local watersheds. Local, place-based advocacy projects that are strongly grounded within their geographical area have the potential to inspire environmental change as citizens come together to collectively address environmental challenges in their own neighborhoods. However, less attention has been given to these small, intensely place-based local projects. Our resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Jennifer Preece et al (35) describe community-driven environmental projects as an emerging form of citizen science. These locally led small groups who have physical meetings, facilitated by mobile applications and web sites, take on projects that directly benefit their communities.…”
Section: Overview Of the Eventsmentioning
confidence: 99%
“…Jennifer Preece et al (35) describe community-driven environmental projects as an emerging form of citizen science. These locally led small groups who have physical meetings, facilitated by mobile applications and web sites, take on projects that directly benefit their communities.…”
Section: Overview Of the Eventsmentioning
confidence: 99%
“…Previous work has shown that a strong partnership among scientists and citizens has great potential to prompt decision making and produce policy changes [11]. For instance, The Community-Driven Environmental Project co-designed its technology platform, NatureNet, with naturalists and community members to successfully support local watershed management, such as engaging residents in installing rain barrels [9]. When connected to CCS, sustainable HCI further explores how researchers take on the role of supporters that facilitate utilizing and disseminating technology, instead of supervisors that oversee and control the entire community engagement procedure.…”
Section: Community Co-designmentioning
confidence: 99%
“…It is inspired by community-based participatory research 11 and popular epidemiology, 12 in which citizens directly engage in gathering data and extract knowledge from these data for advocacy and activism. Examples involve co-designing technology for local watershed management, 13 understanding water quality with local communities, 14 , 15 and using geo-information tools to monitor noise and earthquakes. 16 CCS intends to extend the scope of previous frameworks to Sustainable Development Goals, especially the goal of sustainable cities and communities.…”
Section: Introductionmentioning
confidence: 99%